2016
DOI: 10.1007/s00436-016-5009-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium delichoni n. sp.: description, molecular characterisation and remarks on the exoerythrocytic merogony, persistence, vectors and transmission

Abstract: Malaria parasite Plasmodium (Novyella) delichoni n. sp. (Haemosporida, Plasmodiidae) was found in a widespread Eurasian songbird, the common house martin Delichon urbicum (Hirundinidae). It is described based on the morphology of its blood stages and segments of the mitochondrial cytochrome b and apicoplast genes, which can be used for molecular identification of this species. Erythrocytic meronts and gametocytes are strictly nucleophilic, and mature gametocytes possess pigment granules of markedly variable si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…These phylogenetic reconstructions based on both Bayesian and likelihood methods found a sister relationship between Plasmodium and Parahaemoproteus . To summarize previous research, four articles supported a Parahaemoproteus /subgenus Haemoproteus sister relationship (Valkiūnas et al 2010, 2016; Palinauskas et al 2015; Lutz et al 2016), five articles supported a Plasmodium / Parahaemoproteus sister relationship (Martinsen et al 2008; Santiago-Alarcón et al 2010; Martinezde la Puente et al 2011; Pacheco et al 2018) and one article obtained mixed results depending on the taxa, evolutionary model and genes analyzed (Borner et al 2016). Pacheco et al (2018) bears special mention as the most recent study with the largest dataset in terms of complete mitochondrial genes (Pacheco et al 2018).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These phylogenetic reconstructions based on both Bayesian and likelihood methods found a sister relationship between Plasmodium and Parahaemoproteus . To summarize previous research, four articles supported a Parahaemoproteus /subgenus Haemoproteus sister relationship (Valkiūnas et al 2010, 2016; Palinauskas et al 2015; Lutz et al 2016), five articles supported a Plasmodium / Parahaemoproteus sister relationship (Martinsen et al 2008; Santiago-Alarcón et al 2010; Martinezde la Puente et al 2011; Pacheco et al 2018) and one article obtained mixed results depending on the taxa, evolutionary model and genes analyzed (Borner et al 2016). Pacheco et al (2018) bears special mention as the most recent study with the largest dataset in terms of complete mitochondrial genes (Pacheco et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, the authors found Plasmodium as a paraphyletic clade (Lutz et al 2016). Recent work by Valkiūnas describing a new malaria parasite Plasmodium delichoni included phylogenetic analyses describing a sister relationship of the subgenus Haemoproteus and Parahaemoproteus , and a more distant relationship with Plasmodium (Valkiūnas et al 2016). Finally, work by Pacheco et al (2018) used 114 complete mitochondrial genomes of many taxa to infer the relationships of haemosporidians for the genera Leucocytozoon, Plasmodium, Haemoproteus and Hepatocystis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to see phanerozoites in some Novyella species even if parasitaemia is high [2, 4, 130–132]. Recent histological studies, combined with chromogenic in situ hybridization diagnostic tools indicate that exo-erythrocytic development in some tropical Novyella species is mainly primary, and the persistence of infection is due to long-lasting light parasitaemia [133]. In other words, merozoites developing in erythrocytic meronts of these parasites might be unable or have limited ability to produce phanerozoites.…”
Section: Resultsmentioning
confidence: 99%
“…One blood film from each bird was rapidly stained and examined microscopically, as described by Valkiunas et al (2016). One nightingale infected with an unidentified lineage of P. matutinum was determined and used for the strain isolation during this study.…”
Section: Collection Of Blood Samplesmentioning
confidence: 99%